Isolation, identification, and pathogenicity tests of pathogenic bacterial associated with black body syndrome in white barramundi Lates calcarifer B. - Akmal Izwar; Sri Nuryati; Rahman; Rini Purnomowati (Jurnal Akuakultur Indonesia, 2020)
ABSTRACTThis study aimed to obtain the pathogenicity of isolated bacteria from maribund barramundi Lates calcarifer with black body syndrome (BBS). Moribund barramundi was collected from the Center for Mariculture Development (BBPBL), Lampung Province. Five of pathogenic bacteria were found, i.e. Pseudomonas stutzeri L01, Vibrioharveyi, Bacillus cereus, Salinococcus roseus, and Pseudomonas stutzeri L02. The bacteria were tested for LD50 to obtain two types of high virulent bacteria to be used for the pathogenicity test. P. stutzeri L01 and V. harveyi were the most virulent bacteria with a bacterial density of 107 CFU/mL. Both bacteria were used for pathogenicity test with three treatments: injection of P. stutzeri L01, V. harveyi, mix P. stutzeri L01 and V. harveyi, and phosphatebuffered saline as control. Clinical symptoms showed a blackened body, bleeding under the belly, and inactive. Mortality of fish injected with P. stutzeri L01, V. harveyi and mix P. stutzeri L01 and V. harveyi was 53.33%, 55.00%, and 58.33%, respectively. Erythrocyte and hemoglobin in all treatments were not significantly different (P>0.05). However, there was significantly different in the total leukocytes of mixed P. stutzeri and V. harveyitreatment (P<0.05). In conclusion, P. stutzeri L01, V. harveyi and mix of them resulted in black body syndrome (BBS) disease. Coinfection of P. stutzeri L01 and V. harveyi produce higher mortality than single infection.Keywords: barramundi, black body syndrome, histopathology, pathogenicityABSTRAKPenelitian ini bertujuan mendapatkan patogenisitas bakteri dari ikan kakap putih L. calcarifer yang memiliki gejala black body syndrome (BBS). Ikan diambil dari Balai Besar Pengembangan Budidaya Laut (BBPBL), Lampung. Lima jenis bakteri patogen ditemukan, yaitu Pseudomonas stutzeri L01, Vibrio harveyi, Bacillus cereus, Salinococcus roseus, dan Pseudomonas stutzeri L02. Bakteri diuji LD50 untuk mendapatkan dua jenis bakteri virulen tinggi yang akan digunakan untuk uji patogenisitas. P. stutzeri L01 dan V. harveyi adalah bakteri paling virulen dengan kepadatan bakteri 107 CFU/mL. Uji patogenisitas dengan tiga perlakuan: injeksi P. stutzeri L01, V. harveyi, campuran P. stutzeri L01 dan V. harveyi, serta phosphate-buffered saline sebagai kontrol. Gejala klinis menunjukkan tubuh menghitam, perdarahan di bawah perut, dan pergerakan tidak aktif. Mortalitas ikan yang disuntik dengan P. stutzeri L01, V. harveyi dan campuran P. stutzeri L01 dan V. harveyi masing-masing sebesar 53,33%, 55,00%, dan 58,33%. Eritrosit dan hemoglobin pada semua perlakuan tidak berbeda nyata (P>0,05). Namun, ada perbedaan yang signifikan dalam total leukosit perlakuan campuran P. stutzeri L01 dan V. harveyi(P<0,05). P. stutzeri L01, V. harveyi dan campuran P. stutzeri L01, V. harveyi dapat menyebabkan black bodysyndrome (BBS). Koinfeksi P. stutzeri L01 dan V. harveyi menghasilkan mortalitas lebih tinggi daripada infeksi tunggal.Kata kunci: barramundi, black body syndrome, histopatologi, patogenisitas